Vivências do cuidador familiar de pacientes idosos acamados em atenção domiciliar - Campos, Joice Soares (2020)
In recent years, due to several factors, life expectancy has increased and, due to advances in the health area, people have been living for a longer period, even with some type of disability. Consequently, there has been an expressive growth of caregivers in homes, who may be professionals hired for this or family caregivers. This dissertation is organized in two studies that complement each other, as they appear as excerpts from a research aimed at exploring the experiences of family caregivers of elderly patients bedridden in home care. The first study aims to understand the experiences related to the definition of the role of family caregiver. The second study deals with the mourning and struggles experienced by family caregivers in the face of the care process. The participants were 10 family caregivers of elderly bedridden patients assisted by a home care program in a city in the interior of Minas Gerais. Two instruments were used for data collection: a semi-structured interview script and a field diary. The interviews were conducted individually and recorded on audio. The field diary was used by the researcher to record her impressions during the interviews, especially about the non-verbal behavior of the participants. The corpus was built from the transcripts and, in addition, from the field diary records. The results referring to the first study reveal that family caregivers reported having taken on this role for three basic reasons: due to the illness of the elderly family member, because they saw themselves without choice and / or because they were previously caregivers in other contexts. The results referring to the second study show that the mourning and struggles experienced by family caregivers refer to the loss of the healthy family member and the possibility of their death, in addition to the loss of the previous life, at the family, social and leisure levels. Therefore, both studies emphasize the importance of welcoming family caregivers from the moment the family is faced with the illness of one of their loved ones and needs to choose the family caregiver, so that the one who performs this role can do so in a healthy way.